Surface morphology and optical properties of epitaxial AlxGa1-xN - Kim, JW; Choi, IH; Park, YK; Kim, YT (KOREAN PHYSICAL SOC, 1999)
The surface morphology and absorption edges of epitaxial AlXGa1-XN layers grown on (0001) sapphire substrate by molecular beam epitaxy are investigated with the change of AlN mole fractions. Transmission and photothermal deflection spectroscopy determine the absorption coefficient at room temperature. Photothermal deflection spectroscopy can be applied to determine the low absorbance values. The uniform depth profile and linear dependence of average atomic concentration of epitaxial AlXCa1-X N layers on AlN mole fraction imply that the epitaxial growth of AlXGa1-XN layers with variation of AlN mole fraction is well controlled without the compositional fluctuation in depth of the epilayer. It is observed by atomic force microscopy that the surface grain shape and roughness of epitaxial AlXGa1-XN layers change at a middle of AlN mole fraction, and also observed that the effective bandgaps increase with increasing AlN mole fraction.
Keywords: FIELD-EFFECT TRANSISTOR; STRUCTURE LASER-DIODES; SAPPHIRE; ALGAN